(untitled) (TEST Ticontre. Theory Text Translation, 2017)
The link between translation and migration has become a popular topic in recent studies (De Fina 2003, Cronin 2006, Polezzi 2012, Giordano 2014). These studies put forward the assumption that one of the main effects of migration is the disruption of the grounding of the self in a given mother tongue, as movement across cultures breaks the constitutive relation between language and identity (De Fina 2003:3). Given such hypothesis, these studies investigate what kind of identity is shaped in migratory contexts, and what role translation plays in its shaping. The present paper takes as starting point the assumption that heteronymous translation is a mediated form of communication that reiterates migrants’ difference and deprives them of their voice (Cronin 2006, Polezzi 2012). As translated beings, migrants are subjected to an external act of interpretation and representation, which controls their subjectivity and agency. Therefore, for them, “the right to exercise autonomous forms of translation” – not to receive translation- is a “crucial element in their emancipation” (Cronin 2006:53-54). In this article, I seek to explore the link between self-translation, migration, and identity, through a reading of Duranti’s self-translated novel. I argue that self-translation constitutes an unmediated and autonomous form of communication that returns migrants their voice, thus shaping them as agents – and not receivers- of translation. To this end, firstly, I investigate how the writer redefines and represents her ‘hybrid identity’; secondly, I illustrate how her will to voice her hybrid identity affects the linguistic performance of her self-translation, resulting into a specific translating approach, which aims to ‘hybridise’ the text, in order to mediate affinities and differences. I aim to demonstrate that the intentional hybrid form of her self-translations is part of an ideological operation aiming to enact a hybrid discourse against monolingual positions and purity, in favour of multilingualism and heterogeneity.